Physical model approach in developing and creating critical thinking skills for Engineering Hydrology (CEW541) students / Ir. Nurazwa Muhamad Bashar - Muhamad Bashar, Nurazwa (Unit Penerbitan FKAPP, 2020)
Engineering hydrology (CEW541) subject consist of several chapters including urban storm-water system design (7th Chapter). Students were introduced with the design of flow and mitigation measures for stormwater control mainly in the urban area. In conducting the urban stormwater design, students are required to refer to the specific guideline namely Manual Saliran Mesra Alam (MASMA 2012). One of the main concerns for the urban stormwater system is the workability and functionality of the proposed system in controlling the after-development flow (QPost) in each of the development projects. This control is one of the keys to combat with the flooding problems that occurred frequently throughout the year due to the urbanization impacts.